Contribution of River Mouth Reach to Sediment Load of the Yangtze River. (17th November 2015) - Wang, C.; Dai, S. B.; Ran, L. S.; Jiang, L.; Li, W. T.
Abstract : This paper examined the sediment gain and loss in the river mouth reach of the Yangtze River by considering sediment load from the local tributaries, erosion/accretion of the river course, impacts of sand mining, and water extraction. A quantitative estimation of the contribution of the river mouth reach to the sediment load of the Yangtze River was conducted before and after impoundment of the Three Gorges Dam (TGD) in 2003. The results showed that a net sediment load loss of 1.78 million ton/yr (Mt/yr) occurred from 1965 to 2002 in the study area. The contribution of this reach to the sediment discharge into the sea is not as high as what was expected before the TGD. With impoundment of the TGD, channel deposition (29.90 Mt/yr) and a net sediment loss of 30.89 Mt/yr occurred in the river mouth reach from 2003 to 2012. The river mouth reach has acted as a sink but not a source of sediment since impoundment of the TGD, which has exacerbated the decrease in sediment load. Technologies should be advanced to measure changes in river channel morphology, as well as in water and sediment discharges at the river mouth reach.